Immunology of simultaneous liver and kidney transplants with identification and prevention of rejection - Parajuli, Sandesh; Hidalgo, Luis G.; Foley, David (Frontiers in Transplantation, 2022)
Simultaneous liver and kidney (SLK) transplantation is considered the best treatment modality among selected patients with both chronic kidney disease (CKD) and end-stage liver disease (ESLD). Since the first SLK transplant in 1983, the number of SLK transplants has increased worldwide, and particularly in the United States since the implementation of the MELD system in 2002. SLK transplants are considered a relatively low immunological risk procedure evidenced by multiple studies displaying the immunomodulatory properties of the liver on the immune system of SLK recipients. SLK recipients demonstrate lower rates of both cellular and antibody-mediated rejection on the kidney allograft when compared to kidney transplant alone recipients. Therefore, SLK transplants in the setting of preformed donor-specific HLA antibodies (DSA) are a common practice, at many centers. Acceptance and transplantation of SLKs are based solely on ABO compatibility without much consideration of crossmatch results or DSA levels. However, some studies suggest an increased risk for rejection for SLK recipients transplanted across high levels of pre-formed HLA DSA. Despite this, there is no consensus regarding acceptable levels of pre-formed DSA, the role of pre-transplant desensitization, splenectomy, or immunosuppressive management in this unique population. Also, the impact of post-transplant DSA monitoring on long-term outcomes are not well studied in SLK recipients. In this article, we review recent and relevant past articles in this field with a focus on the immunological risk factors among SLK recipients, and strategies to mitigate the negative outcomes among them.